gamma and alpha chains of human fibrinogen possess sites reactive with human platelet receptors. - Hawiger, J (1982)
Fibrinogen, a clottable plasma protein, agglutinates both prokaryotic cells (e.g., staphylococci) and eukaryotic cell fragments (e.g., platelets) through interaction with specific receptors. To identify the region of the fibrinogen molecule responsible for its interaction with human platelets, we prepared polypeptide chain subunits (alpha, beta, and gamma) of human fibrinogen by reduction and carboxymethylation. A mixture of the chains induced aggregation (clumping) of human platelets separated from plasma proteins and treated with ADP. When individual chains of fibrinogen were tested, gamma-chain multimers caused platelet aggregation at a molar concentration comparable with that of intact human fibrinogen. The beta chain remained inactive, and the alpha chain was 1/4th to 1/5th as reactive as the gamma chain. Monospecific antibody fragments against the gamma chain inhibited binding of 125I-labeled fibrinogen to the human platelet receptor and blocked aggregation of platelets induced by ADP in the presence of fibrinogen or gamma-chain multimers. These results indicate that the gamma chain of human fibrinogen bears the main site for interaction with the platelet receptor.